ENHANCING INDUSTRIAL PRODUCTION GROWTH THROUGH EFFECTIVE USE OF TERRITORIAL DEVELOPMENT RESERVES (International Congress on Economics, Management and Business Studies, 2026)
Enhancing industrial production growth through the effective use of territorial development reserves represents a comprehensive socio-economic and institutional strategy aimed at accelerating industrial output by identifying, mobilizing, and efficiently utilizing latent or underutilized resources within defined territorial units, including regions, districts, and cities. In the context of modern economic transformation, this approach is increasingly recognized as an important alternative to capital-intensive growth models, as it prioritizes efficiency gains derived from internal territorial potential rather than relying exclusively on external investment inflows.
Keywords: developed infrastructure networks, untapped raw material bases, and institutional or organizational inefficiencies